PEMBUATAN GAME PLATFORM ENDLESS RUNNING “Ruiner” BERBASIS WEB - Alex Fenturi; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
Ruiner is an endless running game with the perspestive of top down. This game use keyboard for pc and virtual button for smartphone. In this game, the character has to run as far as possible, while collecting the collectables and avoiding the monster and obstacles. Ruiner has 3D display and played in website. Ruiner was made using the Unity game engine with c# as programming language. This game has only one arena called endless stage. The purpose of this game is to reach high score as possible. Testing is done by Black Box testing, Alpha testing and Beta testing which was held by 37respondent. The test result shows that Ruiner level difficulty was normal, entertaining and has convinience control so the player can play with ease. Most of the respondent was interested to play the game again.